Estudio de mercado y plan de comercialización para exportar carne de cuy (Cavia porcellus) - Pindo Nagua, Faviola Margarita (2024)
In this research it has been observed that in South America there are multiple farms and associations specialized in producing and selling guinea pig meat in various presentations. It is highlighted that the United States is the main consumer of this meat, due to the significant influence of the Latin population that seeks typical foods from their regions of origin. In addition, it has been determined that to export meat products, several requirements must be met, including technical sheets, invoices, shipping guides, packing lists, animal health and national certificates, among others, adapted to the regulations of each country. Likewise, it has been concluded that to design a comprehensive marketing plan, covering positioning, communication and distribution strategies, it is necessary to consider various aspects. These include the context and purpose of marketing, describing the company, the product and the service offered, as well as analyzing the environment, the competition and performing a SWOT analysis. Identifying the target audience and developing a value proposition is essential to define market positioning strategies. Advertising tactics, public relations, network content marketing and marketing experiences have been implemented. The generation of relevant content for each communication, sales and distribution channel is crucial to reach the final consumer, specifically those interested in guinea pig meat. For this work, an important literature review was carried out and two successful cases of the production and marketing of guinea pigs were identified, and through interviews with experts on the subject, it was possible to obtain relevant data and the necessary means to export guinea pig meat.